2008
DOI: 10.1177/0091552108315604
|View full text |Cite
|
Sign up to set email alerts
|

The Institutional Vision of Community Colleges

Abstract: Providing an accessible and adaptable education has become an increasingly daunting task for community colleges. Administrators must formulate adaptive strategies as well as purposefully articulate them. A content analysis of the mission and vision statements from a nationwide sample of community colleges was performed, and key linguistic components found to constitute a well conceived, viable, and easily diffused institutional vision were isolated. The prevalence of these components in comparison to other typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Although mission statements are prevalent across most academic institutions, only one-third of all 4-year colleges and universities possess actual vision statements. Abelman and Dalessandro (2008) found that private schools in general and "religious" private schools in particular are more likely to have vision statements than public institutions, and 2-year colleges are more likely to have vision statements than 4-year institutions. Morphew and Hartley (2006) report that the rhetorical fl avor of mission statements for public and private colleges and universities tend to differ, emphasizing the distinct challenges faced by these types of institutions (see, also, Boerema, 2006).…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 98%
“…Although mission statements are prevalent across most academic institutions, only one-third of all 4-year colleges and universities possess actual vision statements. Abelman and Dalessandro (2008) found that private schools in general and "religious" private schools in particular are more likely to have vision statements than public institutions, and 2-year colleges are more likely to have vision statements than 4-year institutions. Morphew and Hartley (2006) report that the rhetorical fl avor of mission statements for public and private colleges and universities tend to differ, emphasizing the distinct challenges faced by these types of institutions (see, also, Boerema, 2006).…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 98%
“…Some recent empirical scholarship has explored community college degree-granting missions by analyzing institutions’ mission statements rather than looking at actual degree-granting behaviors (e.g., Abelman & Dalessandro, 2008; Ayers, 2005, 2011, 2015). Ayers (2005) found that community college mission statements adhered to neoliberal notions of curricular mission, emphasizing short-term vocational certificates that benefited statewide economic development goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the midst of the debate over the focus of community colleges, historical scholarship has investigated the evolving degree-granting missions of community colleges from an institutional perspective (e.g., Brint & Karabel, 1989; Dougherty, 1994). More recent scholarship has analyzed institutions’ mission statements to evaluate what community colleges say they do (e.g., Abelman & Dalessandro, 2008; Ayers, 2015). Another significant body of research has explored how community colleges have shifted their occupational education emphasis from industrial education to social welfare (e.g., health and protective services), business, and information technology (Grubb & Lazerson, 2004).…”
mentioning
confidence: 99%
“…In a process-oriented approach, Evans (1990) described the endeavors of one community college undergoing the process of formulating a mission statement. In an analysis of 172 community college mission statements, Abelman and D’Alessandro (2008) focused on the extent to which the statement represented a clear, compelling, and shared mission; clarified organizational complexity; addressed relative advantage; and described observable goals. Abelman (2011) utilized a similar framework when analyzing mission statements of tribal colleges.…”
Section: Review Of Related Literature and Theoretical Frameworkmentioning
confidence: 99%